A Pragmatic Account of Rephrase in Argumentation: Linguistic and Cognitive Evidence - Koszowy, Marcin; Oswald, Steve; Budzynska, Katarzyna; Konat, Barbara; Gygax, Pascal (Informal Logic, 2022)
In the spirit of the pragmatic account of quotation and reporting offered by Macagno and Walton (2017), we outline a systematic pragmatic account of rephrasing. For this purpose, we combine two interrelated methods of inquiry into the variety of uses of rephrase as a persuasive device: (i) the annotation of rephrase types to identify locutionary and illocutionary aspects of rephrase, (ii) the crowd–sourced examination of rephrase types to investigate their perlocutionary effects. As it draws on Waltonian insights and on empirical and experimental research on the (mis)use of rephrase, our approach allows us to ground a novel theoretically–informed and data–driven pragmatic account of rephrase.